Learning by using visual arts in the lower primary classes through content integration - Bikić, Sanja (Norma, 2025)
Summary: The Subject of this study is teaching visual arts in primary school and how to, by integrating different school topics, promote visual culture, that develops through this school subject. Improving quality and educational outcomes of visual arts teaching and development pupil’s capabilities, necessary for future life and learning, are the occupation of this paper. In the empirical part of the research, integrative teaching, its usage frequency and its different levels in domain of teaching visual arts in lower grades of primary school were analyzed. It was determined if there is a correlation between the age of the teacher, lenght of service, attending seminars on innovative teaching approaches, teachers art education and other characteristics, with the application of an integrated approach frequency in art classes. To determine the relationship between the variables, a quantitative method in the form of correlative pedagogical research was chosen. A non-standardized electronic questionnaire-scale was used as a research tool for data collection. The sample was selected on a voluntary basis and consists of 100 teachers, employed in primary schools in the North Banat, South Banat and Central Banat districts of the Republic of Serbia in the school year 2019/20. The research has shown that teachers apply integrated teaching based on visual arts to a satisfactory extent. By measuring the correlations between the variables, it was concluded that they are weak. Keywords: visual arts, integrative teaching, visual culture, classroom teaching, learning for the future